The international legal right of children to be heard in proceedings affecting them and implemenation in Ireland - Daly, Aoife (Trinity College (Dublin, Ireland). School of Law, 2011)
This thesis explores the nature of the right of children to be heard in proceedings affecting them as enshrined in the Convention on the Rights of the Child (CRC), the international obligations which it creates, and how this pertains to Ireland. The primary focus of the thesis is i) to elucidate the international right and ii) to determine whether the right is being implemented in Ireland in accordance with the CRC.
Keywords: Law, Ph.D.; Ph.D. Trinity College Dublin.